Comparison Between Lignocaine Intravenous Lignocaine Infusion and Ketorolac in Reducing Postoperative Opioid Requirement in Upper Limb Surgeries - Khan, Umer; Bajwa, Saleem Pervaiz; Hussain, Akhtar; Akram, Muhammad; Ahmad, Mirza Sijeel; Zafar, Junaid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the frequency of opioid requirement, after intravenous lignocaine infusion and ketorolac tromethamine in the upper limb surgeries. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital, Lahore Pakistan, from Oct 2017 to Apr 2018. Methodology: ASA I/II patients of either gender undergoing upper limb surgery were included. Patients were randomly divided into two equal groups, “L” (Lignocaine) and “K” (Ketorolac). In L-group, patients were given intravenous 1.5 mg/kg lignocaine bolus, followed by 2.0 mg/kg/hr infusion during entire procedure; while in K-group, patients were given intravenous 0.5 mg/kg (maximum 30 mg) ketorolac, at induction. The patients were monitored for 12 hours postoperatively and in case of severe postoperative pain (Visual Analogue Scale score >5), rescue analgesia (intravenous Nalbuphine 0.1 mg/kg) was provided. Results: Total eighty patients were included in the study. There was no statistical difference between the two groups with age (p-value 0.823), gender (p-value 0.808) and ASA status (p-value 0.184). There was statistically significant difference between the two groups in terms of opioid requirement at 1-hour (p-value 0.035), 6-hours (p-value 0.032) and 12-hours (p-value 0.035), with K-group showing more requirement as compared to the L-group. Conclusion: Intraoperative administration of intravenous lignocaine infusion is superior to ketorolac in effective postoperative pain management in patients undergoing upper limb surgeries.